2011
DOI: 10.1007/s11695-011-0414-1
|View full text |Cite
|
Sign up to set email alerts
|

Morbidly Obese are Ghrelin and Leptin Hyporesponders with Lesser Intragastric Balloon Treatment Efficiency

Abstract: The importance of ghrelin and leptin in treatment-induced changes was reaffirmed. Ghrelin hyper-response in non-morbidly obese subjects characterized greater short-term treatment efficiency and landmarked an inclination to weight regain. The results suggest a potential pattern of individualization between obese patients according to body mass index towards intragastric balloon or bariatric surgery. Further studies are needed in order to get better insights in the pathophysiologic mechanisms of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
3
19
0
2
Order By: Relevance
“…The decline in plasma leptin levels was similarly reported in three studies with the introduction of the intragastric balloon in morbidly obese patients [14]. The concentration continued to fall at lesser marginal levels until the end of the study.…”
Section: Patients (N = 26) Studied Parameter Pre-operative Base Line supporting
confidence: 69%
See 2 more Smart Citations
“…The decline in plasma leptin levels was similarly reported in three studies with the introduction of the intragastric balloon in morbidly obese patients [14]. The concentration continued to fall at lesser marginal levels until the end of the study.…”
Section: Patients (N = 26) Studied Parameter Pre-operative Base Line supporting
confidence: 69%
“…Biological effects of ghrelin appear to be the opposite of those of leptin, which has been suggested to be the key signal reflecting adipose stores [34].…”
Section: Patients (N = 26) Studied Parameter Pre-operative Base Line mentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have described different plasma hormonal changes after bariatric surgery, but the data on the effect on the omentin and visfatin levels are sparse and conflicting [9][10][11][12][13][14][15][16][17]. Moreover, only a few studies have described hormonal changes, mainly ghrelin and leptin, after endoscopic placement of a balloon into the stomach (bioenterics intragastric balloon, BIB), which is a commonly used procedure, also as bridge therapy to surgery, due to its minimal invasiveness and good tolerability [18,19]. We recently found that in morbidly obese patients, weight reduction induced by BIB was connected with a decrease of leptin plasma levels and transient elevation of ghrelin levels, while the levels of these hormones remained relatively stable in obese patients treated with a low-calorie diet and physical effort [18].…”
Section: Introductionmentioning
confidence: 99%
“…[11] The six months follow up duration is recommended in case of IGB but the regaining of weight is a common outcome on long term follow up of the patients [12].…”
Section: Discussionmentioning
confidence: 99%